Pengaruh Latar Belakang Pendidikan, Skala Usaha, Pengetahuan Akuntansi Terhadap Penggunaan Sistem Informasi Akuntansi Pada UMKM - Nurkafta, Muli (Jurnal Akuntansi UMMI, 2022)
ABSTRACT This study aims to determine the effect of educational background, business scale and accounting knowledge on the use of accounting information systems in MSMEs in the furniture industry in Nagrak Village, Sukabumi Regency. This research is a quantitative research and uses primary data in the form of a questionnaire. The sampling technique was simple random sampling and 54 respondents. The data analysis method used was validity test, reliability test, descriptive statistical test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression and partial test. By testing using SPSS21. The results of the study stated that educational background and accounting knowledge had a positive effect on the use of accounting information systems. Meanwhile, the business scale has no effect on the use of accounting information systems.